Determination of the Thickness of a Resistive Material Layer in a Finite Volume Conductor using Focused Impedance Method (FIM) a simulation study - Al-Quaderi, Golam Dastegir; Ahmed, Sayed Parvez; Rabbani, K Siddique-e (Bangladesh Journal of Medical Physics, 2015)
Focused Impedance Method (FIM) is an innovative and relatively new electrical impedance measurement technique that allows localized measurement of the properties of electrically conducting materials in a volume conductor such as the human body using simple measurement setups. In a previous work, FIM, with dual electrode separation, was used to determine thicknesses of subcutaneous fat layers through experimental study on phantoms and human subjects. The present work, carried out using COMSOL Multiphysics software package, is a finite element simulation study for a similar target object that verifies and extends the results of the previous experimental work. A rectangular box of different heights containing a material of uniform conductivity such as saline together with internally embedded layers of resistive materials of different thicknesses were used for this study. The measured transfer impedance in the FIM method showed marked change with the variation of the thickness of the resistive layer and with electrode separation, showing a point of maximum curvature in the latter. We obtained a calibration curve for the thickness from the electrode separation of this point. This allowed a unique method for the determination of thickness of embedded resistive layers which is more general than what had been done in the previous experimental work. This work will help standardize the application of 4-electrode FIM for determination of the thickness of less-conducting material layer in any finite volume, including determination of fat layer thickness, etc. Bangladesh Journal of Medical Physics Vol.7 No.1 2014 8-23